DEVELOPMENT OF GULLIES ON THE LANDSCAPE: A MODEL OF HEADCUT RETREAT RESULTING FROM PLUNGE POOL EROSION - Flores-Cervantes J.H.; Bras R.L.; Istanbulluoglu E. (My University, 2006)
Head advance due to plunge pool erosion is a common process in gullies incising resistant soils. A model of headcut retreat resulting from plunge pool erosion is developed and implemented in the channel-hillslope integrated landscape development (CHILD) model, an existing three-dimensional landscape evolution modeling framework. The model estimates horizontal headcut retreat as a function of discharge, height of the headcut, upstream slope, and relevant land surface and soil properties for soil erosion. We analyze the sensitivity of headcut retreat to flow discharge, upstream slope and surface roughness, and headcut height. CHILD simulations indicate that headcut retreat is most significant in zones with either gentle slopes or large headcut heigths. Model parameters have contasting effects on the retreat rates depending on the size and depth of the pool beneath the headcut and upstream flow hydraulics, making the process difficult to predict as a function of potographic thresholds and simple geomorphic transport laws. Copyright 2006 by the American Geophysical Union.